Збирання енергії навколишнього середовища для живлення сенсорних мереж з низьким енергоспоживанням - Костюк, С. О. (ХНУРЕ, 2019)
This work is devoted to the application of various energy harvesting technologies in the context of low-power autonomous sensor networks. The various sources of ambient energy were compared in the terms of availability, applicability and amounts of energy available for harvesting. Reviewed the ongoing scientific researches and ready-to-market commercial products that enable energy harvesting from different sources. Reviewed the structure of typical sensor node which uses energy harvesting as the main or secondary source of power, with or without energy buffering using batteries or capacitors.